Agricultural injuries encountered in Giresun, which is an agricultural city of Turkey - Turfan, Selim; Özşahin, Faruk; Uzun, Gökhan; Arslan, Bora; Gürgen, Mustafa Tolga; Kesicioğlu, Tuğrul (The European Research Journal, 2020)
Objectives: This study aimed to determine the demographic and clinical features of gardening injuries in an agricultural city and to provide some suggestions to reduce the incidence of agricultural injuries.Methods: This study assessed 419 gardening injuries that were admitted to the emergency department of Giresun University Prof. Dr. Ilhan Özdemir Training and Research Hospital between June 30, 2015 and November 1, 2015. We retrospectively examined all the documents, x-rays, tomographies, and tomography reports related to the cases.Results: Falls from a height (19.3%), falls (31.5%), foreign body crashes (FBCs) (14.8%), sharp-penetrating object injuries (SPOIs) (29.8%), and motorized/motorless device injuries (MMDIs) (4.5%) were the major categories of gardening injuries. Most of the falls from a height were from a tree (86%), primarily fig trees (54.3%). SPOIs primarily affected the hand-wrist area with 82 cases (65.6%); the most common sharp tools that caused injury were sickle-scythes (47.2%) and axes (35.2%). FBCs frequently affected the eyes (48.4%) and head region (17.7%), and tree branches were the most common foreign bodies causing such crashes (38.7%). MMDIs were caused primarily by haymaker harvester machines (42%). Three cases died (0.7%), and 305 cases (72.8%) were discharged after emergency treatment. Additionally, 115 cases (27.5%) were hospitalized, 11 cases underwent urgent surgery, and 63 cases underwent elective surgery. Using uncuttable gloves, socks, and knee-guards could prevent 88% of SPOIs. Furthermore, eyewear and head guards could prevent 60.1% of FBC injuries.The usage of fall arrest equipment particularly for only fig and pear tree types could prevent 68.6% of the falls from a tree.Conclusions: Gardening injuries are significant traumas in agricultural regions. By implementing simple and cheap security measures, we can prevent destrucitive traumas.